Fighting caravans - Grey, Zane (Vina Distributors, 2004)
Wanted by the law, frontiersman Gary Cooper avoids arrest by persuading a wagon-train girl to pose as his wife. As the train heads west, hostile forces are encountered, romance blooms, and Cooper becomes a hero.